The Impact of Cultural Dimensions on Islamic Students’ Attitude Towards Problem-Based Learning - Esti Zaduqisti (JURNAL PENELITIAN, 2016)
The current study aims to examine the impact of cultural dimensions (i.e., collectivism, power distance, uncertainty avoidance, and masculinity) on students’ attitudes toward problem-based learning. The design of the study was a correlational survey, in which participants were recruited through convenient sampling. Inspection of a multiple regression analysis (N = 549) revealed that collectivism and masculinity positively corresponded with students’ attitudes. In particular, the findings showed that the higher the levels of collectivism and masculinity, the more students supported the implementation of problem-based learning. In contrast, uncertainty avoidance was negatively related to students’ attitudes, such that the higher this cultural dimension, the less students supported problem-based learning. Power distance was the only predictor that did not significantly predict students’ attitudes toward problem-based learning. Overall, these findings suggest the importance of taking into account the characteristics of norms and values held within a country that may contribute to the success, feasibility, and suitability of problem-based learning. Theoretical implications and study limitations are discussed, along with practical strategies highlighting how to address cultural potentials and pitfalls in an effort to promote problem-based learning.